Synthesis and reactivity of group 13 and group 14 dipyrrinato complexes - Gidman, C. E. (2020)
Herein, the synthesis, reactivity, and high pressure crystallographic studies of group 13 and group 14 dipyrrinato complexes is reported. A series of germanium(II) and tin(II) dipyrrinato complexes (3.1–3.14) have been synthesised with varying steric bulk through substitutions of the alpha-position with H, Me or Ph substituent, and at the meso-position with either H, Ph, Mes or Tmp substituent. Synthesis of group 14 dipyrrinato complexes with protons in the alpha- position are achieved via oxidation of the proligands in THF in situ, followed by deprotonation and the addition of 7 equivalents of the metal(II) halide. Whereas germanium(II) and tin(II) dipyrrinato complexes with bulkier alpha-substituents are synthesised via metathesis reactions between the lithium dipyrrinato complex and the metal(II) halide in THF. This lead to the first metal(II) complex stabilised by the ligand dipyrromethene (2.1). Complexes 3.4 and 3.7 were studies by high pressure crystallography. A series of homoleptic and heteroleptic gallium(III) dipyrrinato complexes (2.4-2.8) have been synthesised in a similar manner, via metathesis reactions with the lithium dipyrrinato complex and the metal(III) halide, and by varying the ratio of ligand to halide gives either the homoleptic or heteroleptic gallium(III) dipyrrinato complex. The BODIPYs 2.1-2.3 were synthesised and characterised by 1H, UV/Vis and fluorescence spectroscopy to allow comparison of optical and electrochemical properties of the metal complexes.